#TITLE_ALTERNATIVE# - HARTONO (NIM 23498015), MOH.
Through its development, quality control focus has been showing a movement from product and process control to an earlier stages, the product and process design. In related with Taguchi's method which quality problems is minimized loss by biased controlling and variance reduction that only can be done in design stages. Researchers are still arguing and discussing the Taguchi's contributions especially regarding the orthogonal design and signal to noise as performance measure. Many literature have shown that Response Surface Methodology is one among others that has been consider potential as an alternative to Taguchi approach, although it recent concerns still on static quality characteristic. This research pays attention on dynamic characteristic system involving signal factor in injection molding process. It will cover three activities, i.e. (i) the best quality (target) is determined based on both the signal and the response, (ii) the resulted quality loss is measured by the deviations from target, and (iii) selection of parameter is determined by response surface method. The signal factor in injection molding process is the mold dimension in relation to different molded products. In this case, robust design methodology can be used to make the process robust to the family of product.